Análisis jurídico y doctrinario de la mediación escolar como medio hacia una cultura de paz - Abad Alverca, Erika Cesive (2024)
The present research work entitled “Legal and doctrinal analysis of school mediation as a means towards a culture of peace” is carried out because school mediation is an alternative and effective mechanism for the solution of school conflicts that also contributes to the prevention of school violence by educating in a culture of peace; but it does not have a real institutionalization in the National Education System. Thus, the members of an educational community, especially children and adolescents, are deprived of an instance to solve their school conflicts with the help of a school mediator, who can also correspond to a member of the educational institution, when this is their will and due to the nature of the conflict it is possible to resort to this mechanism; it is important to analyze and consider that school mediation must have a special and detailed legal framework that supports and guides its institutionalization, as it happens in the foreign legislations of Spain, Argentina and Mexico. It is worth mentioning that, by providing for institutional school mediation as an alternative means of conflict resolution, it is not intended to be a means of delay or evasion of responsibility, but rather to guarantee through it the principle of the best interest of the child; the right to education; the right to personal integrity, which includes a life free of violence in the public sphere; and the right to a culture of peace. Thus, the objective of this paper is to carry out a legal and doctrinal study of the contribution of school mediation to move from a culture of direct punishment and violence towards a culture of peace, analyzing and verifying the benefits of its institutionalization, given the high educational component implicit in it, mainly aimed at building a culture of peace.